Numerical simulation and analysis of crack disease in tunnel lining structure - Chen, Song; Yang, Zhao; Liu, Shuo; Li, Liufang; Zheng, Yibo; Yuan, Ying (Frontiers in Materials, 2022)
Tunnel construction in China is increasing year by year. With the passage of time, China will usher in the peak period of tunnel engineering repair, and it is vital to study in advance the influential nature of tunnel lining crack disease as well as management measures. By summarising a large amount of relevant literature, this paper analyses the main locations where cracks are generated in tunnel linings. Through the method of finite element numerical analysis, 24 cases of cracks of different widths and depths were modelled and calculated for each location of lining vaults, shoulders and side walls, respectively, to analyse the influence of different cases on the internal forces and deformation of the lining. The study shows that the stress concentration around the crack tip decreases with the increase of the crack width, while the stress concentration around the crack tip increases with the increase of the crack depth. The stresses in the other main parts of the lining increase after the crack is created, which has a deteriorating effect on the load-bearing capacity and stability of the lining structure. With the increase in crack width and depth, the sinking deformation of the vault and the heaving deformation of the back arch increase, especially when the cracks are large, but lining cracking has less effect on the lateral deformation of the lining. Compared to cracks in the top and shoulder of the arch, cracks in the side walls have a more pronounced effect on the distribution of internal forces around the cracks.